Plasma concentrations of diclazuril following oral administration of diclazuril and diclazuril sodium salt to cattle. Issue 4 (30th April 2022) - Dirikolu, Levent; Lehner, Andreas Fritz; Tobin, Thomas
Abstract: Diclazuril is a triazine‐based antiprotozoal agent widely used in veterinary practice that may have clinical application in the treatment of bovine protozoal diseases. The present study reports on the bioavailability, pharmacokinetics, and metabolism of diclazuril and diclazuril sodium salt in cattle following administration of diclazuril suspended in water and by direct application of diclazuril sodium salt to the oral mucosa. Compared with diclazuril itself, the sodium salt formulation of diclazuril applied to the oral mucosa was rapidly and reliably absorbed. Plasma concentrations of diclazuril peaked at around 8 h after oral‐mucosal administration of diclazuril sodium salt. On the contrary, application of diclazuril itself orally resulted in delayed and variable absorption. The mean bioavailability of diclazuril as pure powder was 42.5% relative to diclazuril sodium salt indicating approximately 2.5‐fold increase in bioavailability of diclazuril as a sodium salt relative to diclazuril as a pure compound in cattle. The present study also reports finding of a previously unreported diclazuril metabolite at high concentrations in plasma especially after oral administration of diclazuril. Further studies, including synthesis and characterization of the novel described metabolite, are required to accurately determine aspects of the metabolism of diclazuril in cattle.